Commentary: 20 years online with “Your Disease Risk” - Colditz, Graham A. (Cancer Causes Control, 2020)
The Your Disease Risk tool (yourdiseaserisk.wustl.edu) went live to the public in January 2000 and was one of the first personalized health risk assessment sites on the Internet. Its launch marked the culmination of years of work by a large, multi-disciplinary university team whose primary goal was to translate the science on cancer prevention into accurate, engaging, and useful messages for the public. Today, 20 years on, Your Disease Risk has expanded from its initial four cancers to include 18 different tools designed for today’s users. This commentary reviews important moments and lessons learned in the first two decades of Your Disease Risk. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10552-020-01356-3) contains supplementary material, which is available to authorized users.